P153 Tuberculosis-associated immune reconstitution inflammatory syndrome management. (11th November 2022) - David, D; Dedicoat, M
Abstract : Introduction and Objectives: Tuberculosis-associated immune reconstitution inflammatory syndrome (IRIS) has been described in both HIV-positive and HIV-negative patients, and can be fatal. Corticosteroids have been used in the treatment of TB-IRIS, but not always successfully, as many cases are corticosteroid-refractory and long-term therapy has multiple side effects. As there are no official management guidelines, other therapeutic options need to be identified. The aims of this review are to identify studies supporting the use of immunotherapy, host-directed therapies (HDT), or corticosteroids in TB-IRIS management. Methods: A systematic literature review of studies describing TB-IRIS management has been conducted, limited to the English language. Case reports, case series, observational studies and randomized controlled trials were included. Results: 232 articles describing 974 patients (909 adults and 65 children) were selected from 3100 reports. HDT and immunotherapy types have been identified in 377 patients (354 adults and 23 children) described in 63 papers. These include: corticosteroids, tumor necrosis factor-α antagonists, thalidomide, lenalidomide, interleukin-1 receptor antagonists, interleukin-2, vascular endothelial growth factor inhibitors, various immunosuppressant and antineoplastic drugs, chloroquine derivatives, montelukast, pentoxifylline, paracetamol and non-steroidal anti-inflammatory drugs. Corticosteroid therapy only for TB-IRIS was identified in 96 papers describing HIV-negative patients, and 89 papers describing HIV-positive patients. Conclusion: More evidence is needed to support the management of TB-IRIS, to evaluate the efficiency and safety profile of HDT and immunotherapy in this context.